Polityka rozwoju obszarów wiejskich w Polsce na przykładzie inicjatywy Leader - Borowiec, Agnieszka (Development Policy of Rural Areas in Poland on the Example of the Leader Initiative, 2009)
The paper is an attempt to describe the role of public sector, especially local government and institutions and local organizations - LAGs, in creating and developing Polish traditional products. The author analyzes the meaning of Leader in Poland and shows that the initiative is an efficient method of involving local communities in the process of co-deciding of the direction and implementation of a concept for the development of their rural areas. Perhaps this initiative is an important way to the revitalization and transformation of the Polish village. The Leader+ initiative covers the period of 2000--2006 and includes only 15 Member States. However, the new Member States were given the option to implement Leader+ type measures for the remaining period of the programme since they joined the EU in May 2004. Six out of the ten new Member States have decided to implement these measures in their Objective 1 programmes (2004-2006): the Czech Republic, Estonia, Lithuania, Latvia, Hungary, and Poland. Local Action Groups (LAGs) are made up of public and private partners from the rural territory, and must include representatives from different socio-economic sectors. They receive financial assistance to implement local development strategies through awarding grants to local projects. They are selected by the managing authority of the Member State, which is either a national, regional or local, private or public body responsible for the management of the programme. It is very important that each development plan must be structured around one of themes: the use of know-how and new technologies to make the products and services of rural areas more competitive, improving the quality of life in rural areas and adding value to local products, in particular by facilitating access to markets for small production units via collective actions and making the best use of natural and cultural resources. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 525-533